A review of Australian Cymadusa (Crustacea: Amphipoda: Ampithoidae) with descriptions of eight new species - Peart, Rachael A. (Zootaxa, 2007)
Cymadusa is a large genus of large bodied, predominantly tropical ampithoid amphipods. Prior to this paper 22 species were recognised in Cymadusa of which four were known from Australia. Eight new species are described from Australia, increasing the known Australian species to 12. The new species described herein are: C. chuawe sp. nov. , C. elegantis sp. nov. , C. heronensis sp. nov. , C. jiigurru sp. nov. , C. pemptos sp. nov. , C. thagaay sp. nov. , C. tishana sp. nov. and C. wistari sp. nov. Ampithoe flindersi Stebbing, 1888 is synonymised with Cymdusa setosa (Haswell, 1879). Diagnoses and a key to the Australian species are provided.